2021
DOI: 10.1093/nar/gkab072
|View full text |Cite
|
Sign up to set email alerts
|

Power-law behavior of transcription factor dynamics at the single-molecule level implies a continuum affinity model

Abstract: Single-molecule tracking (SMT) allows the study of transcription factor (TF) dynamics in the nucleus, giving important information regarding the diffusion and binding behavior of these proteins in the nuclear environment. Dwell time distributions obtained by SMT for most TFs appear to follow bi-exponential behavior. This has been ascribed to two discrete populations of TFs—one non-specifically bound to chromatin and another specifically bound to target sites, as implied by decades of biochemical studies. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 75 publications
7
126
0
Order By: Relevance
“…This process could assign biologic activity to GR:GRE interactions that are not clearly linked to changes in gene transcription in linear genomic space, yet increase transcription of enhancer RNAs, whose direct function in transcriptional regulation is not yet fully defined. Moreover, weak interactions between GR and chromatin ( 122 ), which have been variably reported at repressed regulatory regions ( 111 ), could result from close three-dimensional nuclear proximity of repressed regions with sites of canonical GR:GRE interactions. Irrespective of the underlying mechanism, as reviewed by Schmidt et al ( 112 ), numerous signaling cascades ( e.g.…”
Section: Repression Of Inflammatory Gene Expressionmentioning
confidence: 99%
“…This process could assign biologic activity to GR:GRE interactions that are not clearly linked to changes in gene transcription in linear genomic space, yet increase transcription of enhancer RNAs, whose direct function in transcriptional regulation is not yet fully defined. Moreover, weak interactions between GR and chromatin ( 122 ), which have been variably reported at repressed regulatory regions ( 111 ), could result from close three-dimensional nuclear proximity of repressed regions with sites of canonical GR:GRE interactions. Irrespective of the underlying mechanism, as reviewed by Schmidt et al ( 112 ), numerous signaling cascades ( e.g.…”
Section: Repression Of Inflammatory Gene Expressionmentioning
confidence: 99%
“…Following isolation of the bound segments, the next step is to quantify the duration of TF/DNA interactions. Confounding effects brought by slowly diffusing molecules [22,29] and by photobleaching [37] have led to multiple methods to extract the distribution of residence times from SMT data, ranging from long-exposure acquisitions to blur out non-chromatin bound molecules [29], to multi-temporal scale acquisitions, to correct for bleaching [21,38]. Despite these methodological differences, the resulting distribution of residence times is often analyzed in terms of a multi-exponential decay (Figure 2B).…”
Section: Intranuclear Single Molecule Tracking: Analyzing Tf Bindingmentioning
confidence: 99%
“…Furthermore, at least some exogenous [42] and endogenous [43] TFs can display a non-exponential power-law distribution of residence times, blurring out the distinction between specific and non-specific events. At the moment, it is unclear whether the observed differences are biological (different factors behaving differently) or technical (caused by the different methods used to acquire, correct and analyze the residence times distribution, [37]). Therefore caution is recommended when comparing residence time measurements obtained by different groups on different proteins.…”
Section: Intranuclear Single Molecule Tracking: Analyzing Tf Bindingmentioning
confidence: 99%
“…In particular, the importance of the TF residence time in determining the transcriptional burst duration 6,10,11 and size 6,10 has been demonstrated. It has also been shown that association and dissociation are complex processes [12][13][14][15][16][17][18][19] , that cannot be described as simple second-and first-order reactions, respectively. TFs find their targets by coupling three-dimensional diffusion in the solution with one-dimensional diffusion while bound nonspecifically to DNA 20 , and most are unable to bind nucleosomal DNA, so the association time is affected by the genomic context of the binding site 21,22 and by a kinetic competition with nucleosomes 23 .…”
Section: Introductionmentioning
confidence: 99%